Perancangan Company Profile Berbasis Web Untuk Roemahkita Modern Retail Menggunakan Framework Codeigniter - Nurdianto, Afrinda; Sutaji, Deni (Jurnal Sosial Teknologi, 2025)
RoemahKita Modern Retail is a retail business that requires a digital promotional medium to enhance branding and expand customer reach. This project aims to design an informative, interactive, and responsive company profile website using the CodeIgniter framework. CodeIgniter was chosen due to its ease of development, organized structure, and robust security features. The system development methodology includes needs analysis, design, implementation, and testing. The outcome of this project is a company profile website that displays company information, products, galleries, and contact details. The website is designed with a user-friendly interface and is optimized for accessibility across various devices. The use of CodeIgniter enables efficient development with its MVC (Model-View-Controller) architecture, which separates business logic and presentation layers. This website is expected to serve as an effective promotional tool for RoemahKita Modern Retail in introducing its business to potential customers. For future development, additional features such as e-commerce integration, SEO optimization, and enhanced system security can be implemented.